Cost-Sensitive Self-Paced Learning With Adaptive Regularization for Classification of Image Time Series - Hao Li (IEEE, 2021)
The classification of image time series has potential significance in the field of land-cover analysis with the increasing number of remote sensing images. The key problem of the classification of image time series is how to transfer the already available knowledge on the source domain to the target domain. Nevertheless, most of the existing methods do not consider the impact of different sample costs on the classifier during transferring. In addition, it is very difficult to collect reliable labeled samples with changed or unchanged categories between the source domain and the target domain in the case of a large number of training samples. In order to alleviate the above problems, we propose a cost-sensitive self-paced learning (CSSPL) framework with adaptive regularization for the classification of image time series in this article. Considering that the costs of different samples cannot be completely equal to the classifier, different cost values are assigned to each type of error first, then we minimize the total cost to give the change detection classifier a preference on the unchanged class, aiming to reduce wrong label propagation from the source to the target image. Besides, an adaptive mixture weight regularizer is designed to automatically assign sample weight based on the loss value of the dataset, which enables more reliable sample weights to be selected for training. Experimental results show that the proposed algorithm provides a set of reliable samples for the training of classifier and achieves a promising improvement on classification accuracy.